2021
DOI: 10.3390/ijerph182413111
|View full text |Cite
|
Sign up to set email alerts
|

Fear of Coronavirus, Stress and Fear of Childbirth in Polish Pregnant Women during the COVID-19 Pandemic

Abstract: The COVID-19 pandemic is the largest pandemic of an aggressive coronavirus in the human population in the 21st century. The pandemic may have a negative emotional impact on pregnant women, causing fear and stress. Negative feelings during pregnancy later affect fear of childbirth. Our study aimed to determine the relationship between fear of COVID-19, stress and fear of childbirth. We assume that fear of COVID-19 will be a mediator of the relationship between perceived stress and fear of childbirth. A total of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 52 publications
(84 reference statements)
3
32
1
2
Order By: Relevance
“…Studies were also conducted which, similar to this research, found that fear of COVID-19 was at a medium level in patients (Dymecka et al, 2021;Is ¸ıklı et al, 2022;Sahu et al, 2021;Sürme et al, 2021). It is noticeable that, according to the findings of this study and the literature results, the fear of COVID-19 continues to be at a medium level among patients.…”
Section: Discussionsupporting
confidence: 83%
“…Studies were also conducted which, similar to this research, found that fear of COVID-19 was at a medium level in patients (Dymecka et al, 2021;Is ¸ıklı et al, 2022;Sahu et al, 2021;Sürme et al, 2021). It is noticeable that, according to the findings of this study and the literature results, the fear of COVID-19 continues to be at a medium level among patients.…”
Section: Discussionsupporting
confidence: 83%
“…Stepowicz et al [ 25 ] showed that levels of stress and anxiety in pregnant or postpartum women during the pandemic were moderate to high. In other studies conducted in Poland during the pandemic, a moderate and positive relationship among women was observed between perceived stress, fear of COVID-19 and fear of childbirth [ 24 ]. Ilska et al [ 26 ] noted that during the second wave of the pandemic, almost 38.5% of pregnant women reported high preparedness stress and 26% reported high perinatal infection stress.…”
Section: Discussionmentioning
confidence: 99%
“…Cronbach’s alpha reliability index for the PSS-10 is 0.86 (Polish version) [ 38 , 39 ]. The PSS-10 scale can be used to assess the perceived stress in women during the perinatal period [ 8 , 24 , 25 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The significantly higher level of fear of COVID-19 in pregnant women compared with non-pregnant women is likely the result of the health and economic complications affecting pregnant women during the pandemic outbreak, as well as uncertainty about the effects of COVID-19 on the fetus. Research shows that pregnant women fear both continuing the pregnancy and endangering their own lives and the need to terminate the pregnancy as a result of infection because they believe they are more likely to develop a severe course of infection and that the infection could be transmitted to their unborn child [ 56 ]. Negative feelings and emotions can influence pain perception and increase pain perception [ 57 ].…”
Section: Discussionmentioning
confidence: 99%